Molecular identification of rhizospheric Actinomycetes from karst ecosystems of Gorontalo, Indonesia, and its seed germination induction capability of Zea mays var. doti - YULIANA RETNOWATI; ABUBAKAR SIDIK KATILI; NOVRI YOULA KANDOWANGKO; WAWAN PEMBENGO (Society for Indonesian Biodiversity, 2024)
Abstract. Retnowati Y, Katili AS, Kandowangko NY, Pembengo W. 2024. Molecular identification of rhizospheric Actinomycetes from karst ecosystems of Gorontalo, Indonesia, and its seed germination induction capability of Zea mays var. doti. Biodiversitas 25: 4763-4771. Karst, as an extreme ecosystem, was a source of diverse Actinomycetes with varied biological activities. This study explored the plant-growth-promoting potential of rhizospheric Actinomycetes from the karst ecosystem of Gorontalo, with a focus on inducing seed germination in Zea mays var. doti. Four locations in Gorontalo were selected to explore Actinomycetes, targeting approximately 20 different rhizospheric plant species to isolate these microorganisms. Among the 25 isolates obtained, representing diverse morphological types from 12 rhizospheric plants, eight actinomycete isolates exhibited phosphate-solubilizing activity and produced indole-3-acetic acid (IAA). The 16S rRNA gene sequence analysis showed that approximately 75% of the isolates belonged to the Streptomyces genus, including Streptomyces cavourensis strain KRZm-02, Streptomyces sp. strain KRZm-03, Streptomyces pratensis strain KRLl-01, Streptomyces carpaticus strain KRIt-01, Streptomyces sp. strain KRIt-02, and Streptomyces aquilus strain KRPa-01. Additionally, 12.5% of the isolates were identified as Nocardiopsis alba strain KRZm-01 and Micromonospora sp. strain KRPt-01, respectively. The two isolates with the highest plant-growth-promoting potential, Streptomyces pratensis strain KRLl-01 and Streptomyces carpaticus strain KRIt-01, were further tested for their ability to promote germination of Zea mays var. doti seeds over 7 days. Among the two, Streptomyces carpaticus strain KRIt-01 exhibited the highest germination-inducing potential. Overall, the karst ecosystem of Gorontalo offers a valuable reservoir of biological resources with the potential for Plant-Growth-Promoting Rhizobacteria (PGPR). Further studies on the application of these actinomycete isolates as biofertilizers in agricultural and plantation crops could significantly contribute to improving crop growth and productivity, thereby revolutionizing agricultural practices.